Investigation on Mechanical Properties of Hybrid Polymer Composite Reinforced by Rice Husks and Date Palm Fibers as a Construction Material - Salih, Sihama Issa; Jasim, Aseel Subhi; Hasan, Ammar Mousa (Al-Nahrain Journal of Science, 2018)
In this study the boards were fabricated from unsaturated polyester resin reinforced by rice husk and date palm fibers, with the total volume fraction of reinforcement materials was(30%) using different value of filler loading including the ratios (0/30, 5/25, 10/20 15/15, 20/10, 25/5 and 30/0) for volume fraction of date palm fibers/ rice husk, two groups of the hybrid composite were prepared depending on the length of palm fibers, the first group have palm fibers its length 2-3 mm and second group have short fibers its length less than 1mm. The fabricated boards were evaluated for the mechanical properties (tension, compression, flexural, and impact tests) for all the prepared samples were studied. The results from this work show that all of these properties increase with increased the volume fraction of palm fiber at the expense of the proportion of rice husks in hybrid composite. Decreasing the length of fibers from (2-3mm) to micro-sized length (less than 1mm) increased the mechanical properties of flexural strength, maximum shear stress, flexural modulus, and fracture toughness of the prepare composites. Moreover the mechanical properties of the polyester composite reinforced with date palm fibers gave better mechanical properties than the polyester composite reinforced with rice husk.